Rescue for the dead : the posthumous salvation of non-Christians in early Christianity - Trumbower, Jeffrey A., 1960- (New York : Oxford University Press, 2001)
"Christianity is a religion of salvation in which believers have always anticipated some type of post-mortem bliss. This has usually meant non-salvation for others, in the form of eternal torment, alienation from God, or annihilation at some point after death. A self-understanding as a set-apart community of the saved (or potentially saved) has been a hallmark of Christian communities since their earliest days, and the Christian imagination in the West has usually drawn a sharp boundary at death. If someone did not join the saved community during this life, joining it after death would be impossible." "In this book, Jeffrey Trumbower examines how and why death came to be perceived as such a firm boundary of salvation. Analyzing exceptions to this principle from ancient Christianity, he finds that the principle itself was slow to develop and not universally accepted in the Christian movement's first four hundred years. In fact, only in the West was this principle definitively articulated, due in large part to the work and influence of Augustine. Many early Christians were able to retain their sense of having been "chosen" and their sense of God's justice while allowing for the possibility of posthumous salvation for non-Christians (a doctrine that survives among modern Latter-day Saints, who practice posthumous baptism for this purpose). Many others argued vehemently against posthumous salvation, however, and Trumbower documents the development of that conflict and its resolution in the East and in the West."--BOOK JACKET.
Greek, Roman, and Jewish succor for the dead. Methodological considerations ; Archaeology of grave sites ; Epitaphs ; Feeding the dead ; Providing a proper burial ; Rescue for the dead in a "salvation" context -- The New testament and other early Christian literature. Paul ; Luke 16:19-31 and 2 Clement 8 ; I Peter 3:19-20 and 4:6 ; Shepherd of Hermas, Similitudes 9.16 and Epistula Apostolorum 27 ; Apocalypse of Peter 14:1-4 and Sibylline Oracles 2:330-38 -- Thecla's Prayer for Falconilla. The Acts of Paul and Thecla in the context of the Acts of Paul ; Thecla as woman and confessor ; Falconilla as dream figure and recipient of grace ; Later interpretations of the Thecla/Falconilla tradition -- Perpetua's prayer for Dinocrates. The historical Perpetua ; Events leading up to the Dinocrates visions ; The Dinocrates visions ; Events following the Dinocrates visions ; The new prophecy movement, Perpetua, and Dinocrates ; Later interpretations of the Dinocrates visions -- Jesus' descent to the underworld. Jesus' descent ; Posthumous rescue for ancient righteous ones ; An offer of salvation for all the dead ; Varying opinions in the fourth and fifth centuries ; The Gospel of Nicodemus -- Posthumous progress and universal salvation. Gnostic speculations on posthumous enlightenment and reincarnation ; Origen ; Gregory of Nyssa ; Later history of universalism in the east -- Augustine's rejection of posthumous salvation for non-Christians. Antecedents to Augustine ; Views of the early Augustine ; Augustine's rejection of universal salvation ; Interpreting Jesus' descent to Hell ; The debate with Vincentius Victor over Perpetua and Dinocrates ; The mature Augustine -- Gregory the Great's prayer for Trajan. Gregory's Dialogues ; The Gregory/Trajan Story in east and west ; Trajan, Falconilla, and posthumous salvation in west and east ; Trajan and Falconilla at the Council of Ferrare/Florence through the present day.
Includes bibliographical references (p. 177-190) and indexes.
Keywords: Salvation after death -- History of doctrines -- Early church, ca. 30-600.; Salvation outside the church -- History of doctrines -- Early church, ca. 30-600.